Financial reforms in Taiwan : 1960 - 1993 - Teo, Melvin Tzai Win (2014)
Despite Taiwan's extraordinary economic performance over the past three decades, her financial system has been underdeveloped and inefficient. Contrary to popular belief that financial liberalisation and deepening are growth enhancing policies, Taiwan's experience has demonstrated that the existence of an efficient informal market could also facilitate rapid real growth. Nevertheless, in recent years, both domestic and international developments have coerced Taiwanese authorities to undertake measures in reforming the financial sector.